Hostile Media or Hostile Source? Bias Perception of Shared News. (February 2018) - Yun, Gi Woong; Park, Sung-Yeon; Lee, Sooyoung; Flynn, Mark A.
An experiment was conducted with college students to examine the effects of source and user comments on the perceptions of a shared news story embedded in a blog post. When the shared news was credited to a news organization source incongruent with the participants' political orientation, it was perceived to be biased against the participants' issue position. When credited to a congruent source, the same news was perceived to be biased in favor of the participants' position. In addition, the shared news from an incongruent source was perceived to have greater influence on others' issue position than the same news from a congruent source, although perceived reach of the shared news was not different between the two conditions. A subsequent regression analysis identified source and perceived influence, but not perceived reach, as predictors of news bias perception. On the other hand, the second factor, user comments either agreeable or disagreeable to the participants' issue position, did not influence how the shared news was perceived. In the discussion, theoretical implications of these findings are elaborated, and suggestions are made to refine the methods of shared news research.